Parenting of Working Mothers of Providing Food Intake on The Growth of Preschool-Aged - Salsabilla Aulia Jatmiko; Suryati (Politeknik Kesehatan Kemenkes RI Jakarta I, 2022)
Growth is necessary for everyone in stage of life. Preschool age is 3-6 years which are they have a critical phase inchildren, the surrounding environment have to support children. Career Woman have dual role as worker andhousewives. Career Woman have less attention to their children in the growth of stage, which is mothers have animportant role to providing care. This study used a descriptive analytic method with a cross sectional approach. Thesamples taken in this study were 67 people, using simple random sampling technique. The results of the study based onthe results of the Chi Square test obtained p value = 0.450 > ? = 0.05 refers to Ho failed to be rejected or accepted,meaning that there is no relationship between food intake and the growth of preschool-age children in East CilebutVillage. One of the major factors is the nutritional status of children is parenting style. Mothers has crucial role in leadhealthy eating to maintain established children feeding patterns. Based on this phenomena, increase knowledge isnecessary for build good parenting for career woman, through education and health promotion such as conductcounseling about spending time with their children. To increase children's growth, mothers could use effective variouskinds of therapheutic games.